Potato cultivar Etola exhibits hypersensitive resistance to PVYNTN and partial resistance to PVYZ‐NTN and PVYN‐Wi strains and strain‐specific alterations of certain host miRNAs might correlate with symptom severity. (15th September 2016) - Yin, Z.; Xie, F.; Michalak, K.; Pawełkowicz, M.; Zhang, B.; Murawska, Z.; Lebecka, R.; Zimnoch‐Guzowska, E.
Abstract : This study demonstrates the new sources of resistance available in potato cv. Etola, which represent multiple strain‐specific resistance genes against three strains of Potato virus Y (PVY). Etola is the first documented cultivar of this sort in Europe that exhibits hypersensitive resistance (HR) to PVY NTN isolate PVY‐3202, and different levels of partial resistance to PVY N ‐Wi isolate PVY‐3411 and PVY Z ‐NTN isolate PVY‐3303. The isolate PVY‐3411 induced severe symptoms and faster systemic viral coat protein and RNA accumulation in the noninoculated upper leaves, whereas PVY‐3303 caused mild symptoms and delayed viral spreading. This study provides the first example of strain‐specific alteration of a set of host microRNAs (miRNAs) and their targets in the potato–PVY interaction. The tested miRNAs and targets are altered only in plants of cv. Etola infected with PVY‐3411 but not those infected with PVY‐3303 nor PVY‐3202. The up‐regulation of stu‐miR162, stu‐miR168a and miR172e, together with their target transcripts, DCL1, AGO1‐2 and TOE3, respectively, in PVY‐3411‐infected plants correlates with high abundance of HC‐Pro RNA encoding an RNA‐silencing suppressor and might be linked with the severe symptoms in leaves. Moreover, PVY‐3411 causes parallel increases in two members of stu‐miR482 and their mRNA targets Gpa2 and CC‐NBS‐LRR that are involved in the defence response.